Legal and Ethical Challenges in Developing Islamic Financial Products : A Contemporary Perspective - Nawawi Yazid; Muhammad Nawawi (Al-Hiwalah: Journal of Sharia Economic Law, 2025)
The development of Shariah-compliant financial products has become an integral part of the global banking and finance industry. This article examines the legal and ethical challenges faced in the development of Shariah-compliant financial products from a contemporary perspective. These challenges include strict adherence to Shariah principles, effective supervision and regulation, as well as ethical considerations in handling customer funds. In the context of the evolving financial technology (fintech) innovation, this article also explores how Shariah-compliant financial products can harness this technology without compromising the integrity of Shariah principles. Additionally, we identify recent trends and changes in Shariah-compliant financial products and analyze the social and economic impact of successful development in this area. This article also presents innovative approaches and solutions to address the legal and ethical challenges encountered, with the aim of promoting sustainable growth of Shariah-compliant financial products in line with Shariah principles. This research is expected to provide valuable insights to financial practitioners, regulators, and researchers interested in the development of Shariah-compliant financial products in the contemporary era.